2016
DOI: 10.1523/jneurosci.1069-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deletion of Astroglial FMRP Dysregulates Glutamate Transporter GLT1 and Contributes to Fragile X Syndrome Phenotypes In Vivo

Abstract: How the loss of fragile X mental retardation protein (FMRP) in different brain cell types, especially in non-neuron glial cells, induces fragile X syndrome (FXS) phenotypes has just begun to be understood. In the current study, we generated inducible astrocyte-specific Fmr1 conditional knock-out mice (i-astro-Fmr1-cKO) and restoration mice (i-astro-Fmr1-cON) to study the in vivo modulation of FXS synaptic phenotypes by astroglial FMRP. We found that functional expression of glutamate transporter GLT1 is 40% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 50 publications
4
88
0
Order By: Relevance
“…Loss of function or over-expression of these molecules has been shown to affect spine pathology. A recent study showed that Fmr1 deletion in astrocytes in vivo reduced expression of the major glutamate transporter, GLT-1, which normally functions to control extracellular synaptic glutamate levels (47). Loss of GLT-1-mediated glutamate uptake elevated the level of extracellular glutamate and consequently increased the excitability of layer V pyramidal neurons (19, 47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function or over-expression of these molecules has been shown to affect spine pathology. A recent study showed that Fmr1 deletion in astrocytes in vivo reduced expression of the major glutamate transporter, GLT-1, which normally functions to control extracellular synaptic glutamate levels (47). Loss of GLT-1-mediated glutamate uptake elevated the level of extracellular glutamate and consequently increased the excitability of layer V pyramidal neurons (19, 47).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Fmr1 deletion in astrocytes in vivo reduced expression of the major glutamate transporter, GLT-1, which normally functions to control extracellular synaptic glutamate levels (47). Loss of GLT-1-mediated glutamate uptake elevated the level of extracellular glutamate and consequently increased the excitability of layer V pyramidal neurons (19, 47). As raised local glutamate concentration may promote de novo spine growth (48), dysregulated glutamate homeostasis induced by the loss of FMRP in astrocytes may partially account for the increased spine formation observed in global and astrocyte-specific Fmr1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since glia play crucial roles in synapse development and plasticity, it is not surprising that misregulated astrocytes and microglia underlie the pathological mechanisms at work in many neural disorders. Inclusively, glial cells may regulate the pathology of Rett syndrome [55], Down syndrome [56], Spinal Muscular Atrophy [57], Fragile X syndrome [58] and others [59]. Surprisingly, abnormal phenotypes can be rescued or alleviated by wild type glial cells, even when the neurons still harbor the detrimental mutations.…”
Section: Aberrant Interplay Between Glia and Synapses In Neurologicalmentioning
confidence: 99%
“…This suggests that additional cell types or 152 conditions may be required to unmask synaptic phenotypes in vitro. For example, our inclusion 153 of mouse glia increased the health and viability of our neuronal cultures, but could also reduce 154 phenotypic severity if glia contribute to electrophysiological phenotypes in FXS, as reported in 155 other experimental contexts (29)(30)(31). While our experiments allow us to sensitively reveal 156 phenotypes specific to excitatory cortical neurons, they cannot capture the complex relationship 157 with inhibitory neurons and how this may drive network perturbations.…”
Section: Neurons 127mentioning
confidence: 92%